STYLISTIC FEATURES AND LEXICOGRAPHIC INTERPRETATION OF IRONY IN UZBEK AND ENGLISH LANGUAGES (International journal of artificial intelligence, 2026)
This article discusses the stylistic features and lexical interpretation of irony in Uzbek and English languages. Irony is considered one of the important stylistic devices that enhance emotional expressiveness and pragmatic meaning in speech. The paper analyzes the semantic and stylistic peculiarities of irony, its functions in literary texts, and the problems of translating ironic expressions between Uzbek and English. In addition, the article studies the lexicographic interpretation of irony in explanatory dictionaries and highlights similarities and differences between the two languages. The research is based on comparative and descriptive methods.